Telemedicine System for Monitoring Heart Rate Using Independent Component Analysis in Videos (Latin-American Journal of Computing, 2017)
Heart is the organ responsible for providing blood, oxygen and nutrients through the human body, their initial monitoring was reflected in heart rate value, this measurement is a possible irregularity within the organism. Control of this vital sign in most cases involves help of medical staff or using sensors that need to maintain contact with the skin, these common monitoring methods generate discomfort and nonconformity in newborns, senior adults or patients suffering from skin sensitivity. According these disadvantages, project offers a non-invasive and non-contact system based on telemedicine principles, which provides a quick, reliable and economical remote heart rate monitor. Results are compared with a pulse oximeter with a resolution of 1 bpm and accuracy of ±2%, obtaining low and acceptable errors.